Farmers’ perception on climate change and ecological hazards in Riu and Rapti waterbasin, Chitwan, Nepal - Regmi, H.P.; Regmi, P.P.; Dutta, J.P.; Dangol, D.R. (Journal of Agriculture and Environment, 2018)
A survey research was done to study the farmers’ perception on climate change and ecological hazards in Riu and Rapti water basin, Chitwan, Nepal. Altogether 120 households, 60 from each water basin in Riu and Rapti were selected randomly for the study. Pre-tested interview, direct observation, focus group discussion as well as secondary data from Department of Hydrology and Meteorology (DHM), Kathmandu were used to collect the required information. Majority of the farmers’ perceived the change in climatic condition in their locality in terms of increase in hotter days, decrease in colder days, variability in the number of rainy days, decrease in rainfall duration, increase in amount and intensity of rainfall, late onset and shift of usual monsoon pattern, prolonged occurrences of dry spells, decrease water level in the river as compared to the past decades. Farmers prioritized the floods/riverbank cutting (61.7%) and drought (63.4%) hazards for obtaining immediate solution/adaptation strategies in Riu water basin; and for drought (60%) and loss of wetland and declining water source (45%) in Rapti water basin. Analysis of the climatic data (last 42 years for rainfall and last 30 years for temperature) showed the increasing trend of annual rainfall (6.83 mm per year) and those of both maximum and minimum temperature (0.019°C per year and 0.069°C per year, respectively). These analyses strongly support the farmers’ perception about the climate change and for which immediately effective adaptation mechanism is required.